A resonator inspired by spider web for wave propagation in planar periodic lattice. (May 2022) - Zhao, Pengcheng; Zhang, Kai; Hong, Fang; Deng, Zichen
Abstract: The spider web is a multifunctional structure with vibration transmission performance and excellent mechanical properties. In this study, a spider web-inspired resonator is designed to adjust the band gaps of periodic lattices with different topologies. The spider web-inspired resonator can increase the relative density of periodic lattice and generate multiple local resonant band gaps. The parameter study finds that the band gap distribution can be adjusted by changing the material parameters containing mass density and Young's modulus of spider web-inspired resonator. These results reflect the tunability of the resonator inspired by the spider web to the band gaps of the periodic lattice. The spider web-inspired resonators can also be applied to other periodic lattices. Highlights: A spider web-inspired resonator is designed to adjust the band gaps of periodic lattices with different topologies. The spider web-inspired resonator can increase the relative density of periodic lattice and generate multiple local resonant band gaps, reflecting the tunability of the spider web-inspired resonator for the band gaps. The vibration transmission simulation of the finite lattice confirms the vibration suppression of the periodic lattice with spider web-inspired resonator.